Gen AI for a generative or a creative generation: A gesture of a materialist orientation to contemporary L2 writing? - Md. Saiful Alam; Adelina Asmawi (Interdisiplinary Journal of Pedagogy and Research in Media Technology, 2025)
Background: In this age of omnipresent celebration of generative artificial intelligence (Gen AI) in education, what will happen to humans’ naturally acquired intelligence may be a million-dollar question. From the long-termism perspective and existential and humanistic worldviews, this question stands very relevant and legitimate.Aims: This paper aims to philosophically pose questions as regards the uncritical uses of Gen AI tools and deconstruct the meaning of AI-integrated writing, positing the phenomenon in the generational concern and futurism with the potential formation of writing habitus.Methods: By applying the method of theoretical reflection, this study employs a philosophical analysis and critically engages with the extant literature on GenAI-integrated academic writing. By doing so, the paper brings up the potential materialist perspectives on writing within the emerging discourse around the dominant orientations towards GenAI-assisted writing and thus interprets the implications for writers’ creative agency and cognitive contribution. Result: The analysis reveals that students (digital natives) of the present generation may exhibit a syndrome of being easily gravitated into the materialistic quicksand of the so-called “textual generation” while keeping themselves as “cognitive absentees” in the process of writing as a “knowledge creation.” Students’ overindulgence in availing Chat GPT’s generative service may develop a materialistic “generative habit” in students characterizing them as “faithful slaves” to Gen AI labor and as “intelligent dwarfs.” If this decoupling of natural intelligence from writing keeps fossilizing, the whole generation of student writers may turn into the “practitioners” of GenAI-assisted generation of contents and “escapists” and “skeptics” of creation of knowledge based on the contingency of natural human intelligence.Conclusion: The paper, therefore, advocates that it is high time to bypass the shortsighted, neoliberal triumph of writing as a GenAI-supported product or commodity for attaining marks and grades and, thus, reclaim the dignity and creative credits of students’ real scholarship by reorienting writing as a human intelligence-centric creation of real knowledge.